Yếu tố tình thái trong lời xin lỗi =Modality in apologies /Đặng Thanh Hương. - Đặng, Thanh Hương.
Apologizing is a speech act which is an important strategy in social interaction. Apologizer and apologizee. This writing aims to investigate the language of modality in apologies which reveals the attitude of the apologizer.